Evidence for the Benefits of Melatonin in Cardiovascular Disease - Tobeiha, Mohammad; Jafari, Ameneh; Fadaei, Sara; Mirazimi, Seyed Mohammad Ali; Dashti, Fatemeh; Amiri, Atefeh; Khan, Haroon; Asemi, Zatollah; Reiter, Russel J.; Hamblin, Michael R.; Mirzaei, Hamed (Frontiers in Cardiovascular Medicine, 2022)
The pineal gland is a neuroendocrine gland which produces melatonin, a neuroendocrine hormone with critical physiological roles in the circadian rhythm and sleep-wake cycle. Melatonin has been shown to possess anti-oxidant activity and neuroprotective properties. Numerous studies have shown that melatonin has significant functions in cardiovascular disease, and may have anti-aging properties. The ability of melatonin to decrease primary hypertension needs to be more extensively evaluated. Melatonin has shown significant benefits in reducing cardiac pathology, and preventing the death of cardiac muscle in response to ischemia-reperfusion in rodent species. Moreover, melatonin may also prevent the hypertrophy of the heart muscle under some circumstances, which in turn would lessen the development of heart failure. Several currently used conventional drugs show cardiotoxicity as an adverse effect. Recent rodent studies have shown that melatonin acts as an anti-oxidant and is effective in suppressing heart damage mediated by pharmacologic drugs. Therefore, melatonin has been shown to have cardioprotective activity in multiple animal and human studies. Herein, we summarize the most established benefits of melatonin in the cardiovascular system with a focus on the molecular mechanisms of action.